Finite element analysis of free convection flow with MHD micropolar and viscous fluids in a vertical channel with dissipative effects - B, Suresh Babu; Srinivas, G; Reddy, B.R.K. (Journal of Naval Architecture and Marine Engineering, 2011)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–>In the present study, the vertical channel is divided in to two regions one region is filled with Micropolar fluid and the other region is filled with viscous fluid. The channel is subjected to the transverse magnetic field. The coupled governing equations are solved subjected to the boundary conditions proposed by the previous authors using F.E.M. The results are compared with Kumar et al (2010). It is found that the increase in the magnetic field reduces the micro rotation (N) and velocity and enhances the temperature. Increase in the Eckert (Ec) number, decreases the velocity, temperature and micro rotation. The Nusselt number and shear stress values are also analyzed. DOI: http://dx.doi.org/10.3329/jname.v8i1.5808